Effectiveness and safety of 0·5% colchicine cream vs. photodynamic therapy with methyl aminolaevulinate in the treatment of actinic keratosis and skin field cancerization of the forearms: a randomized controlled trial - Miola, A. C. [UNESP]; Ferreira, E. R. [UNESP]; Lima, T. R.R. [UNESP]; Schmitt, J. V. [UNESP]; Abbade, L. P.F. [UNESP]; Miot, H. A. [UNESP] (Oxford University Press (OUP), 2018)
Background: Skin field cancerization (SFC) is a process that occurs in areas of the skin that have undergone genomic alterations induced by ultraviolet radiation. Actinic keratosis (AK) is a sign of its activity. Objectives: To evaluate the effectiveness and safety of 0·5% colchicine (COL) cream vs. methyl aminolaevulinate photodynamic therapy (MAL-PDT) in the treatment of AK and SFC. Methods: We conducted a randomized, open, intrasubject controlled trial. A total of 36 participants with 3–10 AKs on each forearm were treated with either COL cream (twice daily for 10 days) or a single session of MAL-PDT and were reassessed after 60 days. The clinical evaluation was performed using AK count, forearm photoageing scale (PAS) and AK degree (AKD). Patients underwent central forearm biopsies and histopathological evaluation by keratinocyte intraepithelial neoplasia (KIN) assessment, epithelial atrophy and immunohistochemistry (p53/Ki67). Results: Overall, 50% of patients were male. The mean age was 70·9 years (SD 8·6) and phototypes I and II were predominant (89%). Total clearance was observed in six (17%) forearms treated with COL and seven (19%) forearms treated with MAL-PDT (P = 0·76); partial clearance was observed in 44% of forearms in the COL group and 67% of forearms in the MAL-PDT group (P = 0·07). In both COL and MAL-PDT groups, reductions in PAS (−6% vs. −6%) and AKD (−45% vs. −40%) were observed. KIN normalized in 28% of patients treated with MAL-PDT and 20% of those treated with COL. Epithelial atrophy reduced after treatment (P < 0·01). Expression levels of Ki67 and p53 were also assessed. Mild or moderate adverse effects were similar for both groups. Conclusions: COL 0·5% cream and MAL-PDT are safe and effective for treating SFC.